2018
DOI: 10.1371/journal.pone.0202100
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of organic acids with Campylobacter coli from swine

Abstract: Campylobacter coli is a bacterial species that is a major cause of diarrheal disease worldwide, and Campylobacter spp. are among the top 5 foodborne pathogens in the United States. During food production organic acids (OAs) are often used to remove bacteria from animal carcasses. The interactions of six OAs with 111 C. coli strains obtained from swine and retail pork chops were studied by determining the molar minimum inhibitory concentrations (MICMs) of the C. coli strains, and the pH at the MICMs. The Hender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 43 publications
6
44
1
Order By: Relevance
“…strains found MIC values of 1.5% and 1%, respectively [24]. Campylobacter coli strains isolated from pigs had MIC values of 2048 µg/mL in most of the strains tested in the presence of butyric acid and propionic acid [25], lower than the MIC values observed in this study.…”
Section: Antimicrobial Activity Of Short Chain Fatty Acidscontrasting
confidence: 82%
“…strains found MIC values of 1.5% and 1%, respectively [24]. Campylobacter coli strains isolated from pigs had MIC values of 2048 µg/mL in most of the strains tested in the presence of butyric acid and propionic acid [25], lower than the MIC values observed in this study.…”
Section: Antimicrobial Activity Of Short Chain Fatty Acidscontrasting
confidence: 82%
“…) and Campylobacter coli (Beier et al . ), the levels of dissociated acids were closely correlated with the MIC M s of the bacteria in all studies. It also has previously been shown that a fully dissociable acid will cause the disintegration of the bacterial LPS layer (Alakomi et al .…”
Section: Introductionsupporting
confidence: 58%
“…But we have previously shown that Gram‐negative pathogenic bacteria are inhibited by dissociated OAs, and not by pH or the undissociated acids alone (Beier et al . , , , , ). Here, we investigate the effects of pH, undissociated OAs and dissociated OAs against Gram‐positive VRE to evaluate the characteristic of OAs that result in VRE inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations